Analisis Manajemen Risiko Pada UMKM Tas Makmur Online Shop Bandung - Anggani, Rahila; Sudariswan, Eris; Rusliana, Triana (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to analyze the risk management applied in the bag UMKM business in Indonesia. Given the high competition and market uncertainty, bag UMKM face various risks that can affect the continuity of their business. This study uses a qualitative approach with in-depth interviews with bag UMKM owners and managers in several major cities in Indonesia. The results of the study indicate that the most dominant risks faced by bag UMKM businesses are financial, operational, and marketing risks. Many UMKM actors do not yet have a structured risk management system, so they rely on experience and intuition in managing risk. In addition, the application of technology and product diversification were also found to be effective mitigation strategies to reduce the impact of risk. This study suggests the need for training and capacity building in risk management so that bag UMKM can be more adaptive and sustainable in facing existing challenges.